International law and cannabis - Kempen, P. H. P. H. M. C. van (Intersentia, 2019)
What legal avenues do states have to regulate cannabis cultivations and trade for recreational use? This question has generated heated discussions in various societies, in political and academic discourses. Several states are considering adjusting or have adjusted their legal and policy approaches towards a more lenient regulation of cannabis cultivation and trade for the recreational user market. Volume I addresses the legal question of to which extent domestic initiatives involving the regulation of cannabis cultivation for recreational use are compatible with the relevant UN narcotic drugs conventions and European Union law. Volume II takes an innovative approach to this issue and approaches the possibility for regulation of cannabis for recreational use from the perspective of positive human rights obligations.